Exploring Silence as an Element of Fluency in L2 English Academic Presentations - Klimczak-Pawlak, Agata (Neofilolog, 2024)
Viewed from the perspective of a monologue, silence may be interpreted as a means of organizing speech for the purpose of leading the listeners and attracting their attention or, alternatively, as a sign of dysfluency and consequently, an obstacle to easy comprehension. The effect depends on the placement of silent pauses and their function, a criterion that becomes particularly relevant in the case of non-native speech. This paper explores the development in the use of silent pauses by EFL students enrolled in a coursein academic presentation. The three participants selected for the study represent different general EFL proficiency levels. They participated in an academic presentation course during which their presentations at the beginning of the course (an impromptu speech) and after four weeks of specific language-focus training (a prepared short presentation) were recorded. The analysis of the silent intervals in the collected samples reveals differences in the use of silent pauses as an element of dysfluency vs. increased fluency in presenting. The results are discussed from the perspective of fluency measures on the one hand, and successful presentation skills on the other.